Structural response of RC frame under surface curvature and differential settlement in mining areas - Ma, Xiaotong; Bao, Chao; Shang, Haodong; Wang, Huxiang; Doh, Shu Ing; Hu, Jun; Shu, Hongbo (Elsevier Ltd, 2022)
Ground subsidence caused by coal mining can lead to various forms of surface deformation, which endanger the safety of the buildings. To assess the influence of the surface curvature of the mining area on the dynamic performance and damage of surface buildings, the reinforced concrete (RC) frame structures with various differential settlement types are investigated using SAP2000 software. These structures' structural vibration property and damage characteristics are analyzed separately through the modal analysis method, theoretical derivation, and nonlinear static analysis. The result shows that the RC frame structure's natural vibration property and damage degree in the subsidence area vary with negative and positive surface curvature and should not be treated equally. The impact of surface curvatures in mining areas on natural vibration property is the change of structural mass distribution and the stiffness degradation caused by structural damage. The damage caused by the differential settlement will inevitably degrade the seismic performance of the structures located in the subsidence area.